The role of folklore in shaping the Leukonese characters: An anthropolinguistic study - Tasnim Lubis; T. Thyrhaya Zein; Amalia Amalia (Studies in English Language and Education)
This study aims to describe the relationship between folklore and the character of the Leukonese community on Simeulue Island, Aceh Province. Employing an ethnographic and anthropolinguistic approach, the study utilized audio-video recordings of oral Leukonese folklore, including ‘nandong’, ‘nanga-nanga’, and ‘buai’. The performances of ‘nandong’ (songs), ‘nanga-nanga’ (sad stories), and ‘buai’ (poetry) were analyzed using the anthropolinguistic approach to delineate their components (text, co-text, and context) as an integrated whole. The meaning of the folklore was dissected through domain analysis, taxonomy analysis, and semantic componential analysis. Domain analysis explored the semantic relationship between folklore and the Leukonese character, identifying attributes. Taxonomy analysis categorized these attributes, influencing the Leukonese character in performance. Semantic componential analysis served to confirm and annotate these attributes in the Leukonese people’s character. The study’s findings demonstrate that the presence and perpetuation of Leukonese folklore significantly impact the character of its people. ‘Nandong’ teaches (1) the transmission of values and norms, (2) cultural identity and continuity, and (3) social cohesion. Meanwhile, ‘buai’ fosters (1) cultural preservation and celebration, (2) community cohesion and participation, and (3) integration of Malay tradition. Finally, ‘nanga-nanga’ instills (1) emotional expression and coping, (2) the reflection of social realities, and (3) empowerment and voice. Consequently, language serves as a means to express ideas, thoughts, and experiences, manifested in various oral traditions passed down through generations. These traditions often mirror the characteristic patterns of a community.